Analysis of Challenges and Readiness for Competency Certification Testing in the DKV SMKN Tutur Vocational Program - Sheila Ramadani; Isnandar Isnandar; Muhammad Aris Ichwanto (FKIP - Universitas Riau, 2026)
Competency certification ensures vocational quality but encounters hurdles during curriculum shifts. This study analyzes the challenges and readiness of implementing competency certification in the Visual Communication Design (DKV) program at SMKN Tutur during its transition from Multimedia. Employing a descriptive qualitative case study, data were collected via interviews, observations, and documentation from the LSP Head, assessors, teachers, and students selected through purposive sampling. The analysis utilized an interactive model involving data condensation and verification. The results indicate that while the